Y2K: THE END OF THE CENTURY - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
At midnight, December 31, 1999, most computers will change their dates to the year 2000. Some, however, might 'think' that the year has become 1900, and cease to function properly. This is also the case with machines, such as video recorders or...